“Red banditry” as a Socio-Political Phenomenon of the Early 1920s (based on Materials from the Northern Kuzbass) - A. N. Ermolaev (Tsentr nauchnykh i obrazovatelnykh proektov, 2019)
The relevance of the study is due to the presence of conflicts in the social and civil spheres of life both in modern Russia and in the world. A historical excursion into the problem under consideration will help to identify the causes of the confrontation in social conflicts, to develop measures aimed at eliminating and overcoming them. The article discusses the issues associated with the emergence of red banditry in the northern part of the modern Kemerovo region after the end of the Civil War. New archival materials are being introduced into scientific circulation. The novelty of the study is that based on the analysis of the data, the conclusions of researchers involved in the history of red banditry in Siberia are corrected. The author dwells on the facts of the manifestation of red banditry in the Mariinsky district of Tomsk province, reveals the essence of this phenomenon. It is proved that the causes of this phenomenon, in addition to the negative reaction of the Soviet government to the Kolchak regime, the low level of political and spiritual culture of representatives of the new government, the strong influence of partisans, the emergence of a sense of impunity and permissiveness, included such reasons as personal contempt and hostility between ordinary residents, as well as basic desire to appropriate another's property.